Grenada: Education sector survey; An analysis of the education and training system and recommendations for its development - UNESCO (UNESCO)
Against the background of a description of the social and economic conditions in Grenada, this report provides an analysis of the general education system, as well as a discussion of technical and vocational education
Keywords: Mission reports